Indonesia Spirituality and Learning Interest of Papuan Students in Malang - Susanti, Lidia; Kogoya, Sem (the International Journal of Education, Theology, and Humanities, 2022)
Pandemic has forced students to shift to online learning. One of the challenges it poses that teachers need to cope with is student’s interest in learning which affects the mastery of the subject matter taught. Meanwhile, Christian spirituality may play a role in enhancing students’ interest in learning. The research used quantitative ex post facto design. The subject of the research comprised 75 students from Papua who live in Malang. The analysis was conducted using multiple linear regression. The results revealed that Christian spirituality had an effect on students’ interest in learning at 83 percent (R square). It proves that equipping Papuan students spiritually in the knowledge of God impacts on the learning. Keywords: Christian Spirituality, Learning Interest